Proyecto de inversión para la creación de un centro especializado de cuidado y estimulación diaria para niños (as) de 3 meses a 10 años de edad en la ciudad de Loja - Correa Zambrano, Anael Joselin (2016)
Regarding the proposal called "investment project to create a center SPECIALIZED care and stimulation DAILY for children from 3 months to 10 years in the city of Loja" has obtained a lawsuit based on the various changes in social type , cultural and economic have made the role of women housewife fading go over the years, the man was moved causing a single source, which today is increasingly common in families, Mom and Dad work, being very complex that they can devote full time to the care and education of their children, this affects the need for institutions specializing in care for their infants. This work was developed on the basis that meets the needs of the people of Loja, accepting children from 3 months to 3 years with babysitting and from 4 to 10 years with the service tasks directed. Also it met the general objective where the viability of this project is seen as conduct specific market research, develop the technical study, apply the administrative-legal study and carry out the financial evaluation to set the initial investment, revenues, costs and expenses that the company will have. To obtain this project was necessary to start with a market study in which 373 surveys were conducted to determine the babysitting service and 378 surveys to set the service tasks aimed achieving determine supply and unmet demand for childcare there 13,937 potential children who need this service, 13,186 children being the real effective demand as the last 12,024 children and demand directed tasks demand potential is 19,650 children, 15,045 children is real demand and 12,537 children becomes effective demand, also the name for the company called "VIACCHI" and a slogan "Growing and Learning Together" was set, as well as the four P's advertising, price, place and the product was made. With the development of the technical study the functioning and operation of the project was defined as: size here installed capacity, where they develop eight hours a day, having a capacity of 15% per annum for childcare and 25% for tasks executed directed, allowing the company infrastructure capacity also used to be 80% to 107 children attending nursery, and 95 for tasks directed the project location is south of the city in the streets Av Pio Jaramillo between kopernico and Kleper. In performing the financial analysis have a positive Van ensuring a value investment after last 5 years, an internal rate of return that ensures investment since it is higher than the rate of opportunity that offer banking houses, even supports increased costs and decreased 37.12% from 23.69% in revenues this any eventuality that may arise as insertion of new competitors to the market, increasing the level of inflation. With the above it is concluded that the project is profitable for the results and the need that currently exists.